An accidental household outbreak of paliperidone palmitate poisoning via pancake consumption in Lianyungang, China - Tinglu Zhang; Zhentao Li; Peiliang Luo; Qingjun Sun (World Health Organization Regional Office for the Western Pacific, 2020)
Introduction: At 11:20 on 26 May 2018, a physician from Lianyungang No. 1 People's Hospital, China, reported that six family members were being treated in the hospital with symptoms from an unknown cause. Methods: A case series for a food poisoning investigation and an environmental survey were conducted. The patients and their relatives were interviewed in person with a questionnaire contained on a digital tablet, and an investigation of the patients' home was conducted in the presence of police officers. Probable case and confirmed case were defined to serve as a basis for identifying additional cases. Confirmed cases were defined as those probable cases in which blood, stool or vomitus specimens tested positive for paliperidone palmitate and/or its metabolites. A descriptive analysis was performed. Follow-up by telephone was conducted four months later. Results: There were six probable cases. The median age was 35 years (range: 5-76 years). The attack rate was 100% (n = 6/6) of persons who consumed a family dinner, and the hospitalization rate was also 100% (n = 6/6). The median period between exposure and symptom onset was two hours. The main symptoms included vomiting, nausea, drowsiness, dizziness and severe abdominal pain for adults, and vomiting and severe lethargy for children. An 8-year-old girl further showed changes in the ST segment of her electrocardiogram, and a 5-year-old boy showed QT prolongation. The poisoning substance was suspected to be paliperidone palmitate based on the patients' symptoms and epidemiological findings.